A Logic Synthesis Methodology for Low-Power Ternary Logic Circuits - Kim, Sunmean; Lee, Sung-Yun; Park, Sunghye; Kim, Kyung Rok; Kang, Seokhyeong (IEEE transactions on circuits and systems. I, Regular papers, 2020)
We propose a logic synthesis methodology with a novel low-power circuit structure for ternary logic. The proposed methodology synthesizes a ternary function as a ternary logic gate using carbon nanotube field-effect transistors (CNTFETs). The circuit structure uses the body effect to mitigate the excessive power consumption for the third logic value. Energy-efficient ternary logic circuits are designed with a combination of synthesized low-power ternary logic gates. The proposed methodology is applicable to both unbalanced (0, 1, 2) and balanced (−1, 0, 1) ternary logic. To verify the improvement in energy efficiency, we have designed various ternary arithmetic logic circuits using the proposed methodology. The proposed ternary full adder has a significant improvement in the power-delay product (PDP) over previous designs. Ternary benchmark circuits have been designed to show that complex ternary functions can be designed to more efficient circuits with the proposed methodology.